Comparative study between manipulation under anesthesia combined with local steroid injection versus local steroid injection alone in resistant cases of coccydynia - Amer A.M. Elsadek (Wolters Kluwer Medknow Publications, 2023)
Background and aim Coccydynia is pain around and in the coccyx; it is not a diagnosis, but it is symptom. Typically, the affected patients suffer from pain while sitting and particularly when rising from sitting. The current study aims to compare the manipulation under anesthesia combined with local steroid injection versus local steroid injection alone in resistant cases of coccydynia. Patients and methods The present study included 20 patients with coccydynia of different etiologies that unresponsive to medical treatment for more than 3 months. Those patients were classified into two groups: the first group included 10 patents that received a local injection alone. The other 10 patients of the second group had local steroid injection followed by immediate mobilization under anesthesia. The degree of improvement was recorded in every outpatient visit (1 week following the procedure, 1 month later, 3 months later, and after 6 months). Results The obtained results were evaluated according to visual analog scale (VAS) score and ODI. Patients in the first group had 5025+ improved at least two grades on the VAS score two (20%) of them had relapsed and their complaint recurred after 2 months. Another three (30%) patients had recurrence of the original complain after 4 months, that is, 50% of the cases had recurrence. Patients in the second group had improvement of more than four grades in the VAS score with no recorded recurrence, however two of them felt some discomfort for about 2 days after the manipulation that improved spontaneously. Conclusion Manipulation under anesthesia combined with local steroid injection is more superior to local injection alone in management of resistant coccydynia.